Two-Photon Absorption Cooperative Effects within Multi-Dipolar Ruthenium Complexes: The Decisive Influence of Charge Transfers - Durand, Nicolas; Amar, Anissa; Mhanna, Rana; Akdas-Kilic, Huriye; Soppera, Olivier; Malval, Jean-Pierre; Boucekkine, Abdou; Fillaut, Jean-Luc (MDPI, 2022)
One- and two-photon characterizations of a series of hetero- and homoleptic [RuL3-n(bpy)(n)](2+) (n = 0, 1, 2) complexes carrying bipyridine pi-extended ligands (L), have been carried out. These pi-extended D-pi-A-A-pi-D-type ligands (L), where the electron donor units (D) are based on diphenylamine, carbazolyl, or fluorenyl units, have been designed to modulate the conjugation extension and the donating effect. Density functional theory calculations were performed in order to rationalize the observed spectra. Calculations show that the electronic structure of the pi-extended ligands has a pronounced effect on the composition of HOMO and LUMO and on the metallic contribution to frontier MOs, resulting in strikingly different nonlinear properties. This work demonstrates that ILCT transitions are the keystone of one- and two-photon absorption bands in the studied systems and reveals how much MLCT and LLCT charge transfers play a decisive role on the two-photon properties of both hetero- and homoleptic ruthenium complexes through cooperative or suppressive effects.
Keywords: coordination chemistry; ruthenium polypyridyl complexes; two-photon absorption; DFT computations; charge transfer; cooperative effect; NONLINEAR-OPTICAL PROPERTIES; ORGANOMETALLIC COMPLEXES; PHOTOPHYSICAL PROPERTIES; DATA STORAGE; CHROMOPHORES; MOLECULES; DIMENSIONALITY; FLUOROPHORES; FLUORESCENCE; QUADRUPOLAR; Biochemistry & Molecular Biology; Chemistry